The Contribution of Principals’ Leadership Role and Teachers’ Integrity to Elementary School Teachers’ Performance - Verawati Wote, Alice Yeni; Sero, Wiwin Priscilla (International Journal of Elementary Education, 2021)
Teachers have an important contribution in the process of providing quality education. In carrying out their duties, teacher performance is influenced by various factors. This study aims to analyze the contribution of the principal's leadership role and integrity to the performance of elementary school teachers. This research is a quantitative descriptive study using a survey method. The population in this study was elementary school teachers. Sampling using random sampling technique, to obtain a sample of 67 teachers. The data collected in this study used instruments in the form of a principal leadership role questionnaire, a teacher integrity questionnaire, and a teacher performance questionnaire. The data that has been collected is then analyzed using multiple regression analysis techniques. The results showed that the principal's leadership role had a positive and significant effect on the performance of elementary school teachers; teacher integrity has a positive and significant effect on the performance of elementary school teachers; principal's leadership role and teacher integrity simultaneously have a positive and significant effect on the performance of elementary school teachers. This study shows that the good and bad performance of teachers is influenced by the integrity of the teacher and the leadership role of the principal.